2021
DOI: 10.1111/and.13982
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Kombucha against silver nanoparticles‐induced toxicity on testicular tissue in NMRI mice

Abstract: Silver nanoparticles (SNPs) can pass from the cell membrane and testicular blood barrier due to their small size, and by increasing oxidative stress they cause disorder in the male reproductive system. Kombucha is a traditional fermented drink with detoxification and potent antioxidant properties. We aimed to examine the protective effect of Kombucha against the damages due to SNPs on the testis tissue. In this experimental study, NMRI mice were randomly separated into four groups (n = 6), namely control (dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Different studies have proven the improvement effects of SP (300 mg/kg) against toxic metals (Bashandy et al, 2015) and doxorubicin (Eleiwa et al, 2018) in mice and rats. In this study, AgNPs exhibited an increase in MDA level and a decrease in TAC level, our findings were similar to previous research (Elsharkawy et al, 2019; Shariatzadeh et al, 2021). AgNPs promote ROS generation via disruption of the mitochondrial respiratory chain, thereby increase in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different studies have proven the improvement effects of SP (300 mg/kg) against toxic metals (Bashandy et al, 2015) and doxorubicin (Eleiwa et al, 2018) in mice and rats. In this study, AgNPs exhibited an increase in MDA level and a decrease in TAC level, our findings were similar to previous research (Elsharkawy et al, 2019; Shariatzadeh et al, 2021). AgNPs promote ROS generation via disruption of the mitochondrial respiratory chain, thereby increase in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Herein, an increase in the LH level following the AgNPs treated group may be due to the negative feedback of the hypothalamic-pituitary-testicular axis because of reduced in testosterone level, which causes an increase in LH-releasing hormone (LHRH) from the hypothalamus (Rato et al, 2012). Additionally, the previous studies have shown testosterone decrease in the AgNPs treated rodents (Shariatzadeh et al, 2021). However, have reported different results regarding the testosterone alteration induced by AgNPs toxicity (Cavallin et al, 2018;Garcia et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Lipid peroxidation following Ag NP exposure has also been identified in our database. Lipid peroxidation byproducts including malondialdehyde (MDA), and thiobarbituric acid reactive substances (TBARS) have been shown to be significantly increased in serum, testicular tissue or in reproductive cells exposed to Ag NPs [ 46 , 96 , 98 , 103 , 104 ]. ROS-mediated lipid peroxidation is shown in at least two studies out of the 48 studies [ 38 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…In studies examining oxidative stress, the intracellular level of ROS has often been evaluated using a fluorescent probe such as H2-DCF-DA [ 95 , 97 , 105 ]. MDA content in ELISA methods can be used to detect lipid peroxidation, which is one of the main indicators of oxidative stress [ 90 , 94 , 98 ]. With commercial kits, GSH levels and total antioxidant capacities can be measured, as well as analyzed at the level of antioxidant biomolecules and enzymes such as CAT, SOD [ 96 , 104 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herbs such as rosemary are excellent sources of antioxidants with their high content of phenolic compounds. [35]…”
Section: Original Articlementioning
confidence: 99%